Investigating Developmentalism Notions of Development in the Social Sphere - Pathak, Dev Nath.; Das, Amiya Kumar; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
"This book examines development as collective dream, theatre, and performance--focusing on the spectacular case of India and "digital India" as the latest development dream installment. It does so in engaging and deeply probing ways, shedding light on emotional subtexts and undercurrents of developmentalism and modernism, policies and projects, which matter more than is often acknowledged." -Jan Nederveen Pieterse, Duncan Mellichamp Distinguished Professor of Global Studies and Sociology, University of California, USA Compiling various strands of the dis/enchantment with development discourse in contemporary South Asia, with specific focus on the cases from India, this edited book brings together anthropologists, sociologists, economists, and historians to refresh the understanding of development. It introduces ways of thinking "otherwise" about development discourse and what the contributors term "developmentalism"-the social enchantment with development. The cultural discourse of development in contemporary South Asia manifests not only in the official programs of state agencies, but in cinema, television, and mass media. Dear to various stakeholders-from government leaders and manufacturers to consumers and the electorate-is the axiom of a "development(al) society." Organized to bridge familiar understandings of development with radical ways of thinking through developmentalism, this book holds value for those engaged in the anthropology and sociology of development, development studies, South Asian studies, as well as for development professionals working for state and non-governmental organizations.
Chapter 1: Introduction: Developmentalism: On a Trope of (Dis)Enchantment -- Part One: Discontentment and Disenchantment -- Chapter 2: The Danger of Development Today: An Inevitable Polemic -- Chapter 3: The Enchantment of Urbanization: Closer Look at Market's Narrative in Indian Cities -- Part Two: Dramatics and Enchantment -- Chapter 4: The Art of Showing: Imagining Development in Indian Mediascape -- Chapter 5: Crafting Development and Developing Craft: An On-going Dialogue -- Chapter 6: Documentaries and the Development Project: Filmmaking as a Discursive Practice -- Chapter 7: "Tayyari Jeet Ki": The Production of Childhood as a Cultural Trope of Developmentalism -- Part Three: Details of Discontents -- Chapter 8: Development, Marginality, and 'Contested Space' in th eCoastal Kerala, South India -- Chapter 9: Resurgence of Community in the Midst of Despair: Development's Changing Course in Northeast India -- Chapter 10: (Re)producing Middle Class" On Development as Middle Classes Mission -- Chapter 11: Frictions in Resistance: Imagining Post-neoliberal Developmental Possibilities.
Keywords: Developmental psychology; Ethnology; Communication in economic development; Developmental Psychology; Sociocultural Anthropology; Development Communication; Ethnography